Facebook and luxury fashion brands: self-congruent posts and purchase intentions. Issue 4 (3rd April 2020) - Wallace, Elaine; Buil, Isabel; Catalán, Sara
Abstract : Purpose: This study explores consumers' self-congruence with luxury fashion brands they mention on Facebook. It investigates the extent to which those brands are congruent with the actual self (ASC) or the ideal self (ISC), and whether ASC or ISC of luxury fashion brands on Facebook predicts purchase intention. It also examines trait antecedents of both ASC and ISC Facebook mentions of luxury fashion brands, specifically materialism, self-monitoring and self-esteem. Design/methodology/approach: Findings are presented from a survey of Facebook users who mention luxury fashion brands on the social medium. Findings: Self-esteem was revealed as an antecedent of ASC luxury fashion brands mentioned on Facebook, while materialism and high self-monitoring predicted ISC luxury fashion brands. Only ASC luxury fashion brands mentioned online were positively associated with purchase intention. Research limitations/implications: Results are exploratory, and they are limited to those who are active Facebook users and who mention a luxury fashion brand on Facebook. Practical implications: The study offers implications for managers of luxury fashion brands seeking to utilise Facebook to enhance the purchase intention for their brands or to increase the idealisation of the brand. Originality/value: The paper provides new insights into the relationship between self-congruent mentions of luxury fashion brands on Facebook and purchase intention of those brands, distinguishing between ISC and ASC. This research also offers valuable and useful insights into ISC and ASC antecedents.